Dynamics of Dissolution, Killing, and Inhibition of Dental Plaque Biofilm - Wang, Zhejun; Shen, Ya; Haapasalo, Markus (Frontiers in Microbiology, 2020)
The present study aims to establish a standardized model that makes it possible to evaluate the dynamic dissolution of biofilm, killing of biofilm microbes and inhibition of growth of biofilm by disinfecting solutions. Biofilm was grown from dental plaque bacteria on collagen-coated hydroxyapatite (HA) disks for 3 days or 3 weeks under anaerobic conditions. Biofilms were stained with the LIVE/DEAD viability stain and subjected to sterile water, 2% sodium hypochlorite (NaOCl), 6% NaOCl, or 2% chlorhexidine (CHX) for 32 minutes. Dynamic change in fluorescence on bacterial cells and extracellular polymeric substance (EPS) during the exposure was analyzed using Alexa Fluor 647-labeled dextran conjugate and a live-cell imaging confocal laser scanning microscopy (LC-CLSM). The biofilm structures after treatments were visualized by scanning electron microscopy (SEM). The treated biofilms on HA disks were collected and subjected to colony forming unit (CFU) counting. Another set of sterile HA disks were coated with CHX prior to the monitoring of plaque biofilm growth for 12 hours. The LC-CLSM results showed that NaOCl dissolved biofilm effectively, more so at a higher concentration and longer exposure time. Six percent NaOCl was the most effective at dissolving and killing bacteria (e.g. 99% bacterial reduction in 3-day-old biofilm and 95% bacterial reduction in 3-week-old biofilm in 32 minutes) followed by 2% NaOCl and CHX. Sodium hypochlorite dissolved over 99.9% of the EPS whereas CHX only slightly reduced the EPS biovolume in 32 minutes. CFU results indicated that the dispersed biofilm bacteria are more resistant than planktonic bacteria to disinfectants. SEM showed the disruption of biofilm after exposures to CHX and NaOCl. The use of 2% CHX and sterile water did not result in biofilm dissolution. However, prior exposure of the HA disks to 2% and 0.2% CHX for 3 minutes prevented biofilm from growing on the HA disk surfaces for at least 12 hours. This new platform has the potential to aid in a better understanding of the antibiofilm properties of oral disinfectants.